Towards a conceptual framework for developing capabilities of ‘new’ types of students participating in higher education in Sub-Saharan Africa - Buhwamatsiko Tumuheki, Peace; Zeelen, Jacques; Ladaah Openjuru, George (International Journal of Educational Development, 2016)
Building on the participation model of Schuetze and Slowey, this study contributes to the public discourse on theoretical considerations for guidance of empirical research on participation of non-traditional students (NTS) in higher education in Sub-Saharan Africa (SSA). Drawing from empirical work at Makerere University Uganda, we found that improving only the institution environment cannot suffice as there are also other factors affecting participation outside the institutional structures. These include family and work environments and context specific factors like perceptions and socio-cultural environment of the Ugandan society. A conceptual model specific to SSA is thus proposed, and the capability approach presented as the most insightful in elucidating the participation realities of NTS in SSA.
Keywords: Higher education; Non-traditional students; Lifelong learning; Sub-Saharan Africa; Capability approach